2011
DOI: 10.1053/j.gastro.2011.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin S Is Activated During Colitis and Causes Visceral Hyperalgesia by a PAR2-Dependent Mechanism in Mice

Abstract: Background & Aims Although proteases control inflammation and pain, the identity, cellular origin, mechanism of action, and causative role of proteases that are activated during disease are not defined. We investigated the activation and function of cysteine cathepsins (Cat) in colitis. Methods Since protease activity, rather than expression, is regulated, we treated mice with fluorescent activity-based probes that covalently modify activated cathepsins. Activated proteases were localized by tomographic imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
87
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 28 publications
10
87
0
Order By: Relevance
“…Cat-S induced inflammation and pain could also be caused by sensitization and activation of other TRP channels, since PAR 2 can sensitize TRPV1 and TRPA1 and induce neurogenic inflammation and pain (27,31). The finding that Cat-S causes PAR 2 -dependent inflammation and pain is consistent with our previous report that Cat-S causes visceral pain, which required expression of PAR 2 (5). Inhibition of adenylyl cyclase strongly inhibited Cat-S-evoked mechanical hyperalgesia, which implicates PAR 2 biased signaling.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Cat-S induced inflammation and pain could also be caused by sensitization and activation of other TRP channels, since PAR 2 can sensitize TRPV1 and TRPA1 and induce neurogenic inflammation and pain (27,31). The finding that Cat-S causes PAR 2 -dependent inflammation and pain is consistent with our previous report that Cat-S causes visceral pain, which required expression of PAR 2 (5). Inhibition of adenylyl cyclase strongly inhibited Cat-S-evoked mechanical hyperalgesia, which implicates PAR 2 biased signaling.…”
supporting
confidence: 91%
“…We have previously show that Cat-S causes hyperexcitability of nociceptive neurons in wild-type but not par 2 Ϫ/Ϫ mice, but by unknown signaling pathways (5). In the present study we found that Cat-S also reduced the rheobase and increased action potential discharge, confirming hyperexcitability.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…However, it is possible that the inhibition of cathepsin S in the periphery may also contribute and increase the effects of pregabalin and gabapentin. Recently, cathepsin S has been shown to activate PAR2 receptors (Reddy et al, 2010;Elmariah et al, 2014;Zhao et al, 2014), and cathepsin S-induced colonic hyperalgesia in the periphery was suggested to be mediated via PAR2 receptors (Cattaruzza et al, 2011). Less is known about PAR2 receptors in the spinal cord, but specific PAR2 receptor agonists cause mechanical and spinal hyperalgesia when administered intrathecally (Alier et al, 2008), possibly via the inhibition of inhibitory GABAergic neurotransmission (Huang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This increase in activity was coupled with a decrease of mucosal expression of elafin (endogenous elastase inhibitor) in patients with IBD [49]. In mouse colitis, macrophage cathepsins are activated during colitis, and Cat-S activates nociceptors to induce visceral pain via PAR 2 [50]. These different studies demonstrated an increase in proteolytic activity in IBD patients or in mice under experimentally-induced colitis.…”
Section: Endogenous Proteases and Pain Related To Protease-activated mentioning
confidence: 96%